Pharmacological studies of anti-inflammatory, anti-nociceptive and anti-pyretic compounds found in chromatographic fractions of Anogeissus leiocarpa (DC). Guill. & Perr. leaves - Precious A. Idakwoji; Francis O. Atanu; Paul C. Nweje-Anyalowu; Theophilus B. Momoh; Wisdom O. Oniwon; Sara T. Elazab; Souty M.Z. Sharkawi; Rania M. Waheed; Amal Youssef; Gaber El-Saber Batiha (Journal of Pharmacy & Pharmacognosy Research, 2022)
Context: The anti-nociceptive and anti-pyretic properties of the crude aqueous extract of Anogeissus leiocarpa (DC). Guill. & Perr. leaves have been reported.